PERSEPSI PENELITI TENTANG PERPUSTAKAAN BERKELANJUTAN DI LIPI KAWASAN PUSPIPTEK SERPONG (RESEARCHERS PERCEPTIONS ON SUSTAINABLE LIBRARY IN LIPI AREA OF PUSPIPTEK SERPONG) - Yupi Royani; Rahartri Rahartri (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2020)
This study aims to determine the perceptions of the heads of work units and LIPI researchers about the existence and sustainability of libraries in the LIPI Puspiptek Serpong. The study uses descriptive qualitative methods with interview techniques. More in-depth information was collected from the participants, namely the heads of work units and researchers related to the sustainability of the library in the LIPI Puspiptek Serpong. Based on the results and discussions, it was concluded that the library in the LIPI Puspiptek Serpong is still needed both in conventional and digital form because of its function as a repository of knowledge and information sources. As well as its benefits for the community as a place to get information and for researchers to support their research. The library is still needed because as a place to store a collection of books of historical value, management for tacit knowledge (knowledge about research operations) that is not transferred into the finished form such as: books, theses, papers, and as a place of learning for the public. The hope for the LIPI Serpong Library is the realization of an integrated library, where the collections in each work unit are collected into a strategic location. LIPI Serpong library must be able to provide comfort for users.